A honeycomb vanadium tetrasulfide material and its preparation method and application
By controlling the reaction and calcining temperature, vanadium tetrasulfide material with honeycomb 3D structure was prepared, which solved the problem of small contact area of existing electrode materials and improved the conversion efficiency and filling factor of perovskite solar cells.
Patent Information
- Application Number
- CN202310279297.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The contact area between the existing vanadium tetrasulfide electrode material and the electrolyte is limited and the active interface is small, resulting in low photoelectric conversion efficiency and short-circuit current density of perovskite solar cells.
By controlling the reaction temperature and calcining temperature, vanadium tetrasulfide material with a honeycomb 3D structure was prepared, and the specific surface area and carrier transport capability of the material were improved by specific ball milling and scraping methods.
It improves the conversion efficiency and filling factor of perovskite solar cells, enhances the mobility and collection ability of carriers, and extends the service life of the battery.
Smart Images

Figure CN116216777B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and particularly relates to a honeycomb vanadium tetrasulfide material and a preparation method and application thereof. Background Art
[0002] Under the background of dual carbon, the exploration and development of new energy is a current research hotspot. Perovskite materials have unique optoelectronic properties and are therefore widely used in solar cells. Among them, all-inorganic CsPbBr3 perovskite materials have become a research hotspot in the photovoltaic field due to their high stability and simple preparation process. They are light-absorbing layer materials for inorganic perovskite solar cells with commercial potential. However, the photoelectric conversion efficiency of CsPbBr3 perovskite solar cells is low. Therefore, providing an electrode material is an effective strategy to improve the photoelectric conversion efficiency of CsPbBr3 perovskite solar cells.
[0003] Transition metal sulfide electrode materials have high safety and high energy density. By nano-sizing metal sulfides, the battery capacity decay can be slowed down, and the battery's cycle performance and electrochemical properties such as coulomb efficiency can be greatly improved, which has great research significance and value. Vanadium tetrasulfide has a high specific capacity, higher conductivity than oxides, and relatively small electrode polarization, and is a good electrode material. However, the contact area between the vanadium tetrasulfide electrode material prepared by the preparation method provided by the prior art and the electrolyte (mass) is limited, the active interface is small, and its short-circuit current density, conversion efficiency, etc. cannot be well improved. Therefore, providing a vanadium tetrasulfide material and its preparation method is of great significance for improving the conversion efficiency and short-circuit current density of perovskite solar cells. Summary of the invention
[0004] In view of this, the present invention provides a honeycomb vanadium tetrasulfide material and a preparation method and application thereof. By controlling the reaction temperature and calcination temperature, the prepared vanadium tetrasulfide material has a unique honeycomb 3D structure. It is prepared into a counter electrode and applied to perovskite solar cells with excellent conversion efficiency.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] The present invention provides a method for preparing a honeycomb vanadium tetrasulfide material, which comprises at least the following steps:
[0007] Step a, adding a soluble sulfur source and a vanadium source into an organic solvent, stirring and dissolving to obtain a mixed solution, placing the mixed solution in a hydrothermal reaction kettle, reacting at 160° C.-200° C. to obtain a vanadium tetrasulfide solid product;
[0008] Step b: calcining the vanadium tetrasulfide solid product at 250° C.-350° C. under an inert atmosphere, and grinding to obtain the honeycomb vanadium tetrasulfide material.
[0009] Compared with the prior art, the present invention provides a method for preparing a honeycomb vanadium tetrasulfide material, which is conducive to the reaction to form a honeycomb solid by limiting the reaction temperature; the specific calcination temperature can make the honeycomb structure exist stably to form a honeycomb vanadium tetrasulfide material; the present invention controls the reaction temperature and the calcination temperature so that the prepared vanadium tetrasulfide material has a unique honeycomb 3D structure, which has a fluffy structure, a smooth surface, an ultra-thin sheet, a gauze-like shape, and is interconnected, which is conducive to charge transmission and improves the mobility of carriers between interfaces, thereby improving the conversion efficiency of the battery; its unique honeycomb 3D structure also has an extremely high specific surface area, which provides a larger available area for the collection of carriers, and accelerates the transfer of charges to the counter electrode, thereby improving the filling factor and conversion efficiency of the battery.
[0010] Preferably, in step a, the molar volume ratio of the soluble sulfur source, the vanadium source and the organic solvent is 1-2 mol: 3-6 mol: 15-30 mL.
[0011] As a preferred embodiment, in step a, the soluble sulfur source is first dissolved to a colorless and transparent state and then the vanadium source is added and stirred to dissolve until the solution becomes gray-green and turbid.
[0012] The preferred mass volume ratio of the soluble sulfur source, the vanadium source and the organic solvent is conducive to the complete reaction.
[0013] Preferably, the sulfur source is thioacetamide.
[0014] Preferably, the vanadium source is at least one of ammonium metavanadate or sodium orthovanadate.
[0015] Preferably, the organic solvent is at least one of methanol or polyethylene glycol.
[0016] Preferably, in step a, the reaction time is 18h-22h.
[0017] The preferred reaction time is conducive to the formation of a honeycomb structure.
[0018] Preferably, in step a, the temperature is raised to 160°C-200°C by programmed heating, and the heating rate is 3°C / min-8°C / min.
[0019] The preferred heating rate is conducive to the stable formation of the honeycomb structure.
[0020] As a preferred embodiment, in step a, after the reaction is completed, the reaction solution needs to be filtered, washed and dried, and the washing is to wash the filtrate with distilled water and anhydrous ethanol in turn, and the number of washing times is 4-6 times; the drying is a vacuum drying treatment, the drying temperature is 50°C-70°C, the drying time is 10h-12h, and the heating rate during drying is 8-10°C / min.
[0021] Preferably, in step b, the calcination time is 1 h to 3 h.
[0022] Preferably, in step b, the temperature is raised to 250°C-350°C by programmed heating, with a heating rate of 1°C / min-5°C / min.
[0023] The present invention provides a honeycomb vanadium tetrasulfide material, which is prepared by the above-mentioned method for preparing the honeycomb vanadium tetrasulfide material.
[0024] The present invention also provides a counter electrode, comprising the honeycomb vanadium tetrasulfide material.
[0025] The present invention provides a method for preparing an electrode, which comprises at least the following steps:
[0026] Step c, adding the honeycomb vanadium tetrasulfide material and the carbon source into pine alcohol, then adding a binder and a surfactant, and ball milling at a speed of 350 rpm-450 rpm for 10 h-12 h to obtain a honeycomb vanadium tetrasulfide carbon slurry; wherein the carbon source is a mixture of carbon black and graphite;
[0027] Step d: Scrape the honeycomb vanadium tetrasulfide carbon slurry onto a substrate, dry it, and anneal it at 60° C.-90° C. to obtain the honeycomb vanadium tetrasulfide counter electrode.
[0028] The preparation method of the counter electrode material provided by the present invention can improve the conductivity of the carbon slurry by selecting pine alcohol as the solvent of the honeycomb vanadium tetrasulfide material and the carbon source, thereby improving the conversion efficiency of the solar cell; the present invention also limits the rotation speed and time of ball milling, and the specific ball milling conditions ensure that the carbon source can be doped into the honeycomb structure of the vanadium tetrasulfide material to the greatest extent, thereby improving the filling factor of the solar cell; the carbon source is limited to a mixture of carbon black and graphite, thereby further improving the energy density and conductivity of the vanadium tetrasulfide carbon slurry, thereby improving the conversion efficiency of the solar cell; the present invention also adopts a scraping method to scrape the vanadium tetrasulfide carbon slurry with a honeycomb structure on a substrate, thereby enabling the vanadium tetrasulfide carbon slurry to contact the substrate completely and fit tightly, and the counter electrode prepared by using the vanadium tetrasulfide carbon slurry has an excellent honeycomb structure, thereby improving the carrier transmission capacity, thereby improving the conversion efficiency of the solar cell; the specific annealing temperature stabilizes the structure of the vanadium tetrasulfide counter electrode, thereby further improving the service life and conversion efficiency of the battery.
[0029] Preferably, in step c, the mass ratio of the honeycomb vanadium tetrasulfide material, carbon black and graphite is 1-2:1-2:2-4.
[0030] The preferred mass ratio of vanadium tetrasulfide material, carbon black and graphite can maximize the filling factor of the solar cell.
[0031] Preferably, the mass-to-volume ratio of the honeycomb vanadium tetrasulfide material and terpineol is 1:18-20, wherein the unit of mass is g and the unit of volume is mL.
[0032] Preferably, in step c, the adhesive is polyvinyl acetate.
[0033] Preferably, in step c, the surfactant is Triton X-100.
[0034] The preferred surfactant can improve the performance of vanadium tetrasulfide carbon slurry.
[0035] Preferably, in step c, the mass ratio of the honeycomb vanadium tetrasulfide material to the binder is 0.5-1.0:0.2-0.4.
[0036] Preferably, in step c, the mass ratio of the honeycomb vanadium tetrasulfide material to the surfactant is 0.5-1.0:0.1-0.2.
[0037] As a preferred embodiment, in step c, the ball milling adopts a planetary omnidirectional ball mill, and during the ball milling, the zirconium beads are spread all over the bottom of the bottle.
[0038] Preferably, in step d, the drying temperature is 70°C-100°C, and the drying time is 10 min-30 min.
[0039] Preferably, in step d, the annealing time is 20 min-40 min.
[0040] The specific annealing time is beneficial to the stability of the honeycomb structure of the electrode, thereby improving the conversion efficiency of the solar cell.
[0041] Preferably, in step d, the coating thickness is 30 μm-60 μm.
[0042] Preferably, in step d, the substrate is a perovskite light-absorbing layer.
[0043] The present invention also provides application of the counter electrode in a perovskite solar cell.
[0044] The counter electrode provided by the present invention is applied to perovskite solar cells. The excellent 3D structure of the honeycomb vanadium tetrasulfide counter electrode is utilized to improve the contact between the counter electrode and the perovskite back interface, thereby improving the extraction / transmission capacity of carriers at the back interface between the perovskite layer and the counter electrode layer, thereby improving the conversion efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a SEM image of the vanadium tetrasulfide solid product prepared in Example 1 of the present invention;
[0046] Figure 2 This is the JV curve diagram of the counter electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing an electrode, comprising the following steps:
[0050] (1) Weigh 75.1 g (1 mol) of thioacetamide and 350.9 g (3 mol) of ammonium metavanadate, first add thioacetamide to 30 mL of polyethylene glycol, stir until completely dissolved, and the solution is colorless and transparent; then add ammonium metavanadate to the thioacetamide solution, stir at 450 rpm for 3 h until the solution becomes gray-green turbid, to obtain a mixed solution;
[0051] (2) The mixed solution was transferred to the inner lining of a high-pressure reactor, and the reaction was carried out at 160°C for 22 hours, the heating rate was set to 3°C / min, and the pressure in the high-pressure reactor was 1 MPa. After the reaction was completed, the solid compound was filtered and washed with water and anhydrous ethanol in turn for 5 times. After the washing was completed, the drying temperature was set to 50°C in a vacuum drying oven, the heating rate was set to 10°C / min, and the drying was carried out for 10 hours to obtain a solid product of vanadium tetrasulfide.
[0052] (3) calcining the vanadium tetrasulfide solid product at 300°C for 3 hours under a nitrogen atmosphere, with the heating rate controlled at 5°C / min. After calcination, the solid product was ground to a particle size greater than 2000 mesh to obtain a honeycomb vanadium tetrasulfide material;
[0053] (4) Add 70 g of honeycomb vanadium tetrasulfide material, 70 g of carbon black and 140 g of graphite to 1260 mL of pine alcohol, mix well, add 56 g of polyvinyl acetate and 28 g of Triton X-100, grind the above materials in a planetary omnidirectional ball mill, spread zirconium beads on the bottom of the bottle, add the above materials, and ball mill at a speed of 350 rpm for 10 hours to obtain a honeycomb vanadium tetrasulfide carbon slurry;
[0054] (5) The honeycomb vanadium tetrasulfide carbon slurry was scraped onto the perovskite light-absorbing layer, dried at 70°C for 30 min, and annealed at 90°C for 40 min to obtain a honeycomb vanadium tetrasulfide counter electrode with a thickness of 45 μm.
[0055] Example 2
[0056] This embodiment provides a method for preparing an electrode, comprising the following steps:
[0057] (1) Weigh 150.3 g (2 mol) of thioacetamide and 551.7 g (3 mol) of sodium orthovanadate, first add thioacetamide to 25 mL of polyethylene glycol, stir until completely dissolved, and the solution is colorless and transparent; then add ammonium metavanadate to the thioacetamide solution, stir at 450 rpm for 2 h, until the solution becomes gray-green turbid, to obtain a mixed solution;
[0058] (2) The mixed solution was transferred to a hydrothermal reactor and reacted at 200°C for 18 hours. The heating rate was set to 8°C / min. The pressure in the hydrothermal reactor was 0.9 MPa. After the reaction was completed, the solid compound was filtered and washed with water and anhydrous ethanol in turn. The number of washings was 6 times. After the washing was completed, the drying temperature was set to 70°C in a vacuum drying oven, the heating rate was 8°C / min, and the drying was carried out for 12 hours to obtain a solid product of vanadium tetrasulfide.
[0059] (3) In a nitrogen atmosphere, the vanadium tetrasulfide solid product was calcined at 350°C for 1 hour, and the heating rate was controlled at 8°C / min. After the calcination, the solid product was ground to a particle size greater than 2000 mesh to obtain a honeycomb vanadium tetrasulfide material;
[0060] (4) Add 70 g of honeycomb vanadium tetrasulfide material, 35 g of carbon black and 140 g of graphite to 1400 mL of pine alcohol, mix well, add 14 g of polyvinyl acetate and 7 g of Triton X-100, grind the above materials in a planetary omnidirectional ball mill, spread zirconium beads on the bottom of the bottle, add the above materials, and ball mill at a speed of 450 rpm for 12 hours to obtain a honeycomb vanadium tetrasulfide carbon slurry;
[0061] (5) The honeycomb vanadium tetrasulfide carbon slurry was scraped onto the perovskite light-absorbing layer, dried at 100°C for 10 min, and annealed at 60°C for 20 min to obtain a honeycomb vanadium tetrasulfide counter electrode with a thickness of 60 μm.
[0062] Example 3
[0063] This embodiment provides a method for preparing an electrode, comprising the following steps:
[0064] (1) Weigh 90.2 g (1.2 mol) of thioacetamide and 444.5 g (3.8 mol) of ammonium metavanadate, first add thioacetamide to 25 mL of polyethylene glycol, stir until completely dissolved, and the solution is colorless and transparent; then add ammonium metavanadate to the thioacetamide solution, stir at 450 rpm for 2.5 h until the solution becomes gray-green turbid, to obtain a mixed solution;
[0065] (2) The mixed solution was transferred to a hydrothermal reactor and reacted at 250°C for 20 hours. The heating rate was set to 5°C / min. The pressure in the hydrothermal reactor was 1 MPa. After the reaction was completed, the solid compound was filtered and washed with water and anhydrous ethanol in turn for 5 times. After the washing was completed, the drying temperature was set to 60°C in a vacuum drying oven, the heating rate was set to 9°C / min, and the drying was performed for 11 hours to obtain a solid product of vanadium tetrasulfide.
[0066] (3) calcining the vanadium tetrasulfide solid product at 300°C for 2 hours under a nitrogen atmosphere, with the heating rate controlled at 3°C / min. After calcination, the solid product was ground to a particle size greater than 2000 mesh to obtain a honeycomb vanadium tetrasulfide material;
[0067] (4) Add 70 g of honeycomb vanadium tetrasulfide material, 93 g of carbon black and 116.7 g of graphite to 1330 mL of pine alcohol, mix well, add 48 g of polyvinyl acetate and 20 g of Triton X-100, grind the above materials in a planetary omnidirectional ball mill, spread zirconium beads on the bottom of the bottle, add the above materials, and ball mill at a speed of 400 rpm for 11 hours to obtain a honeycomb vanadium tetrasulfide carbon slurry;
[0068] (5) The honeycomb vanadium tetrasulfide carbon slurry was scraped onto the perovskite light-absorbing layer, dried at 90°C for 20 min, and annealed at 70°C for 25 min to obtain a honeycomb vanadium tetrasulfide counter electrode with a thickness of 30 μm.
[0069] Example 4
[0070] Compared with Example 1, the difference between this embodiment and Example 1 is that the amount of graphite used is increased to 300 g, and the other operating steps are the same as those in Example 1.
[0071] Example 5
[0072] Compared with Example 1, the difference between this example and Example 1 is that the time of the thermal reaction of the solution is adjusted to 25 hours, and the other operating steps are the same as those in Example 1.
[0073] Example 6
[0074] Compared with Example 1, the difference between this embodiment and Example 1 is that in step (5), the drying temperature is adjusted to 110° C., and the other operating steps are the same as those in Example 1.
[0075] Example 7
[0076] Compared with Example 1, the difference between this embodiment and Example 1 is that in step (5), the drying temperature is adjusted to 60° C., and the other operating steps are the same as those in Example 1.
[0077] Comparative Example 1
[0078] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (1), the reaction temperature is adjusted to 210° C., and the other operating steps are the same as those in Example 1, and a honeycomb shape cannot be obtained.
[0079] Comparative Example 2
[0080] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (3), the calcination temperature is adjusted to 370° C., and the other operating steps are the same as those in Example 1.
[0081] Comparative Example 3
[0082] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (4), graphite is replaced by an equal amount of graphene, and the other operating steps are the same as those in Example 1.
[0083] Comparative Example 4
[0084] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (4), the ball milling time is adjusted to 14 hours, and the other operating steps are the same as those in Example 1.
[0085] Comparative Example 5
[0086] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (4), graphite is replaced by an equal amount of carbon black, and the other operating steps are the same as those in Example 1.
[0087] Comparative Example 6
[0088] Compared with Example 1, the difference between this comparative example and Example 1 is that in step (4), the annealing temperature is adjusted to 100° C., and the other operating steps are the same as those in Example 1.
[0089] Application Examples
[0090] The counter electrodes prepared in Examples 1-7 and Comparative Examples 1-6 of the present invention were used to perform performance tests on the perovskite solar cells obtained by each treatment. The specific test indicators and test results are shown in Table 1:
[0091] Table 1
[0092]
[0093] As can be seen from Table 1, the counter electrodes provided in Examples 1-7 of the present invention are applied to perovskite solar cells. The excellent 3D structure of the honeycomb vanadium tetrasulfide counter electrode is utilized to improve the contact between the counter electrode and the perovskite back interface, thereby improving the extraction / transmission capacity of carriers at the back interface between the perovskite layer and the counter electrode layer, thereby improving the conversion efficiency of the perovskite solar cell.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a counter electrode, characterized in that: At least the following steps are included: Step a, adding a soluble sulfur source and a vanadium source into an organic solvent, stirring and dissolving to obtain a mixed solution, placing the mixed solution in a hydrothermal reaction kettle, reacting at 160° C.-200° C. to obtain a vanadium tetrasulfide solid product; The molar volume ratio of the soluble sulfur source, the vanadium source and the organic solvent is 1-2 mol: 3-6 mol: 15-30 mL; the soluble sulfur source is thioacetamide; the vanadium source is at least one of ammonium metavanadate or sodium orthovanadate; the organic solvent is at least one of methanol or polyethylene glycol; The reaction time is 18h-22h; Step b, calcining the vanadium tetrasulfide solid product at 300° C.-350° C. under an inert atmosphere, and grinding to obtain a honeycomb vanadium tetrasulfide material; Step c, adding the honeycomb vanadium tetrasulfide material and the carbon source into pine alcohol, then adding a binder and a surfactant, and ball milling at a speed of 350 rpm to 450 rpm for 10 h to 12 h to obtain a honeycomb vanadium tetrasulfide carbon slurry; The carbon source is a mixture of carbon black and graphite; the mass ratio of the honeycomb vanadium tetrasulfide material, carbon black and graphite is 1-2:1-2:2-4; the adhesive is polyvinyl acetate, and the surfactant is Triton X-100; Step d, applying the honeycomb vanadium tetrasulfide carbon slurry on a substrate by scraping, drying, and annealing at 60° C.-90° C. to obtain the counter electrode; The drying temperature is 70°C-100°C.
2. The method for preparing a counter electrode according to claim 1, characterized in that: In step a, the temperature is raised to 160°C-200°C by programmed heating, and the heating rate is 3°C / min-8°C / min.
3. The method for preparing a counter electrode according to claim 1, characterized in that: In step b, the calcination time is 1h-3h; and / or In step b, the temperature is raised to 250°C-350°C by programmed heating, and the heating rate is 1°C / min-5°C / min.
4. The method for preparing a counter electrode according to claim 1, characterized in that: In step c, the mass-to-volume ratio of the honeycomb vanadium tetrasulfide material and terpineol is 1:18-20, wherein the unit of mass is g and the unit of volume is mL.
5. The method for preparing a counter electrode according to claim 1, characterized in that: In step c, the mass ratio of the honeycomb vanadium tetrasulfide material to the binder is 0.5-1.0:0.2-0.4; and / or In step c, the mass ratio of the honeycomb vanadium tetrasulfide material to the surfactant is 0.5-1.0:0.1-0.2; and / or In step d, the drying time is 10 min-30 min; and / or In step d, the annealing time is 20 min-40 min; and / or In step d, the thickness of the scraping is 30 μm-60 μm.
6. A counter electrode, characterized in that: The counter electrode is prepared by the method for preparing the counter electrode according to any one of claims 1 to 5.
7. Use of the counter electrode according to claim 6 in perovskite solar cells.
Citation Information
Patent Citations
Slurry and method for preparing cuprous sulfide counter electrode in sensitized solar cells
CN102298984A
Cited By
Vanadium tetrasulfide catalyst for heavy oil hydrogenation as well as preparation and application of vanadium tetrasulfide catalyst
CN120054532A
MnIn2S4atVS4 heterojunction photocatalyst as well as preparation method and application thereof
CN121016791A